2020
DOI: 10.3389/fimmu.2020.02132
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Storm in COVID-19: “When You Come Out of the Storm, You Won’t Be the Same Person Who Walked in”

Abstract: In December 2019, a novel coronavirus, COVID-19, was discovered to be the causal agent of a severe respiratory infection named SARS-CoV-2, and it has since been recognized worldwide as a pandemic. There are still numerous doubts concerning its pathogenesis and particularly the underlying causes of the various clinical courses, ranging from severe manifestations to asymptomatic forms, including acute respiratory distress syndrome. The major factor responsible for acute respiratory distress syndrome is the so-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 93 publications
(97 reference statements)
0
107
0
3
Order By: Relevance
“…The excessive inflammatory response to COVID-19 infection is regarded as the main pathophysiological triggering event behind mortality and morbidity in infected individuals [6] . Aberrant production of cytokines like TNF-a, IL-1, IFN γ, IL-4, and IL-10 have been reported in severe cases with increased rates of adverse outcomes [23] . For this reason, researchers have been working on novel treatment options focusing on the alteration of immune responses in COVID-19 patients [24] , [25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excessive inflammatory response to COVID-19 infection is regarded as the main pathophysiological triggering event behind mortality and morbidity in infected individuals [6] . Aberrant production of cytokines like TNF-a, IL-1, IFN γ, IL-4, and IL-10 have been reported in severe cases with increased rates of adverse outcomes [23] . For this reason, researchers have been working on novel treatment options focusing on the alteration of immune responses in COVID-19 patients [24] , [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive production of IL-6 is associated with adverse pregnancy outcomes like preterm delivery, preterm premature rupture of the membranes, and chorioamnionitis [31] . Additionally, increased IL-6 levels are observed in severe COVID-19 cases and it is regarded as one of the key actors of the famous ''cytokine storm'' [5] , [23] , [24] . Significantly higher IL-6 levels were found for the study group in the present study and no significant difference was observed between the pregnancy trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory responses can lead to the release of macrophages, monocytes, and other cytokines and chemokines, leading to cytokine storms, thus deteriorating the conditions in COVID-19 patients [ 14 ]. Therefore, inflammatory markers play a crucial role in describing disease severity in COVID-19 patients.…”
Section: Stakeholders Of Sars-cov-2 Mediated Inflammation and Its Marmentioning
confidence: 99%
“…Cytokine storm, bradykinin storm and secondary hemophagocytic lymphohistiocytosis (HLH) have been suggested as potential consequences of COVID-19 infection. [22][23][24] This dysregulated immune response can lead to pulmonary endothelial and alveolar epithelial damage that causes vascular leak and alveolar edema seen in ARDS.…”
Section: Considering the Ards Etiology In Covid-19mentioning
confidence: 99%
“…20,21 There still remain unanswered questions regarding steroid use, although corticosteroid use is now advocated by the as Interferon beta-1b and Emapulumab. 23…”
Section: Anti-inflammatory Therapy In Covid-19mentioning
confidence: 99%